A multicenter retrospective study of early cardiac toxicity in operable breast cancer patients receiving concurrent dual or mono anti-HER2 therapy with postoperative radiation therapy - Jing Yang; Meng-Yun Zhou; Bo Yu; Qing Lin; Yuan Yao; Hua-Ling Wu; Qi-Wei Zhu; Ming Ye; Hua-Ying Xie; Jian-Wei Wu; Gang Cai; Rong Cai; et al. (Breast)
Purpose: This study aims to assess whether dual anti-HER2 therapy with trastuzumab and pertuzumab increases early cardiac toxicity compared to trastuzumab alone in breast cancer (BC) patients receiving postoperative radiation therapy (RT). Methods: Consecutive operable BC patients receiving postoperative RT and trastuzumab with or without pertuzumab between January 2017 and September 2020 at seven tertiary hospitals in China were retrospectively reviewed. Cardiac examinations included echocardiography, electrocardiogram (ECG), NT-proBNP, and cTnI at baseline before RT and during the follow-up. The cardiac event is any new-onset symptomatic heart disease or abnormality in the cardiac examination after RT. Results: In total, 681 patients were enrolled in the analysis, of whom 567 were treated with trastuzumab-alone and 124 patients received dual anti-HER2 therapy. The median follow-up was 11 months. Multivariate analysis showed that left-sided breast cancer (HR 2.38; 95%CI 1.65–3.44, p < 0.001) and IMN RT (HR 1.47; 95 % CI 1.01–2.15, P-value = 0.047) are independent risk factors for ECG abnormalities. Age >50 years is an independent risk factor for developing LVDD (HR 5.16; 95%CI 1.17–22.73, P-value = 0.030). Dosimetric analysis showed that patients who developed subclinical cardiac events had increased mean heart dose (412.0 ± 249.6 vs. 347.2 ± 242.6 cGy, P-value = 0.010). Among right-sided patients or patients receiving anthracycline-based chemotherapy, the dual-targeted cohort had a higher risk of developing ECG abnormalities compared to the trastuzumab-only cohort. Conclusion: Compared with trastuzumab-only, dual anti-HER2 therapy does not increase early cardiac toxicity in combination with postoperative RT in BC patients. Cardiac radiation exposure remains the primary risk factor for early toxicity.